The Sacred Ngider Bhuana Dance in Pengebek ceremony at Banyuning village, Buleleng district, Bali - SUWENDRA, I Wayan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Judging from the preparation, implementation and closing of the Pengebek ceremony, it seems full of the education character values for Hindus. This research was conducted to know for sure about the education character values contained both potential and actual in the process of Ngider Bhuana Dance related to Pengebek Ceremony,.This type of research is qualitative, using a phenomenological approach and symbolic interaction. The data was collected by observation, in-depth interviews, documentation and triangulation. The participants was selected by purposive sampling and the data analysis used content analysis, domains, taxonomics, components, life history, and centralized group discussions.